2018
DOI: 10.2147/ott.s152138
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Zwint predicts poor prognosis and promotes the proliferation of hepatocellular carcinoma by regulating cell-cycle-related proteins

Abstract: IntroductionZwint, a centromere-complex component required for the mitotic spindle checkpoint, has been reported to be overexpressed in different human cancers, but it has not been studied in human hepatocellular carcinoma (HCC).Materials and methodsThe role of Zwint in hepatocellular carcinoma cell proliferation capacities was evaluated by using cell counting kit-8 (CCK8), flow cytometry, clone formation and tumor formation assay in nude mice. Western blot analysis and qPCR assay were performed to assess Zwin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 29 publications
4
66
0
Order By: Relevance
“…Previous studies have examined the expression and roles of ZWINT in multiple types of cancer (7)(8)(9)11,12). Endo et al (10) demonstrated that the interaction of ZWINT with Terf/TRIM17 resulted in its degradation and the consequent regulation of cell proliferation in BC MCF-7 and 293-T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have examined the expression and roles of ZWINT in multiple types of cancer (7)(8)(9)11,12). Endo et al (10) demonstrated that the interaction of ZWINT with Terf/TRIM17 resulted in its degradation and the consequent regulation of cell proliferation in BC MCF-7 and 293-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have proposed that ZWINT acts as a structural protein, which is part of the inner kinetochore scaffold and recruits zeste white 10, which is also a centromere protein, to the kinetochore (5,6). Upregulation of ZWINT has been observed in numerous types of cancer, including ovarian and hepatocellular cancer, as well as glioblastoma, and is indicative of a worse prognosis (7)(8)(9). ZWINT depletion has been demonstrated to attenuate cell proliferation in 293-T and BC MCF-7 cells via Terf/tripartite motif containing 17 (TRIM17) signaling (10).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that abnormal mitosis is a common feature of most malignancies. Although the exact role of the molecular makeup of the kinetochore and how individual components of the kinetochore interact with each other are unknown, growing evidence shows that ZWINT is often highly expressed in a number of human cancers and is linked with poor clinical prognosis and early recurrence (8)(9)(10). However, its role in human GBM remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ZWINT, as a part of kinetochore complex, is a protein interacting with ZW10 that plays essential role in kinetochore-microtubule attachment, spindle assembly check point function and ensures that chromosomes are divided equally between daughter cells (Wang et al, 2004). Recently, overexpression of ZWINT has been reported in human malignancies including prostate, ovarian, lung, and breast cancers, as well as lung cancer and hepatocellular carcinoma (Xu et al, 2016;Ying et al, 2018;Peng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%